Optimizing Footwear Manufacturing Through Defect Analysis and Spare Parts Optimization: Mengoptimalkan Produksi Alas Kaki Melalui Analisis Cacat dan Optimalisasi Suku Cadang - Silmi, Fahmi Amil; Sukmono, Rita Ambarwati; Sriyono, Sriyono; Fitriyah, Hadiah (Indonesian Journal of Innovation Studies, 2024)
This study investigates the causes of defects in the production line of inlay soles in footwear manufacturing, focusing on the impact of malfunctioning machine spare parts. Using Failure Mode and Effects Analysis (FMEA), critical machines—splitting, cutting, and moulding—are identified, along with their associated spare parts influencing defect occurrence. Process FMEA (PFMEA) prioritizes actions based on discussions with maintenance managers and quality staff. Results highlight top spare parts affecting defects, such as Fertinak, grinding stone, and V-belt for the splitting machine; hydraulic motor, hydraulic seal, and hydraulic filter for the cutting machine; and Solid State Relay, Thermocouple, and Heater for the moulding machine. These findings underscore the importance of maintaining machine performance and addressing spare part malfunctions to enhance product quality and operational efficiency in footwear manufacturing, providing actionable insights for industry practitioners. Hightligh: Critical Machines Identified: Splitting, cutting, and moulding machines analyzed for defect occurrence. Spare Parts Influence: Fertinak, Solid State Relay impact defect occurrence. Practical Industry Insights: Strategies for improving product quality and efficiency highlighted. Keywords: Defect analysis, Footwear manufacturing, Spare parts, Failure Mode and Effects Analysis (FMEA), Product quality.